2020
DOI: 10.1111/bjep.12400
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cooperative learning on trait emotional intelligence and academic achievement of Spanish primary school students

Abstract: Increasing the students' academic achievement in the international evaluation arena is a challenge for our country, and cooperative learning and emotional intelligence may be a solution for this problem. The link between cooperative learning, emotional intelligence, and academic achievement has been poorly studied so far. The objective of the present investigation was to examine the influence of cooperative learning on trait emotional intelligence and academic achievement. The methodology used was a quasi-expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
(81 reference statements)
3
6
0
1
Order By: Relevance
“…In this respect, the study's findings are in line with other researchers' insights that cooperative learning improves academic achievement [34][35][36][37]. We can say that being ready to apply the principles of cooperative learning at school on the entire community basis when children learn new things while working in groups or while generalising experience in areas they have already learned [9,11,[34][35][36][37][38][39], we can make great achievements in primary classes. Primary school children are capable and able to work together with others.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this respect, the study's findings are in line with other researchers' insights that cooperative learning improves academic achievement [34][35][36][37]. We can say that being ready to apply the principles of cooperative learning at school on the entire community basis when children learn new things while working in groups or while generalising experience in areas they have already learned [9,11,[34][35][36][37][38][39], we can make great achievements in primary classes. Primary school children are capable and able to work together with others.…”
Section: Discussionsupporting
confidence: 84%
“…It is much harder if a child does not see themselves in that space. In this case, learning can be problematic and irrelevant, not only because it is inaccessible but also because it is not even sought at all [4][5][6][7][8][9]. Research has shown that cooperative learning impacts pupils' social inclusion [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that cooperative learning method has been shown to enhance learning ( Retnowati et al, 2017 ; Carlos Torrego-Seijo et al, 2021 ). Liu et al (2018) conducted a study with 36 non-English major undergraduates.…”
Section: Literaturementioning
confidence: 99%
“…Como se ha indicado, los objetivos son comunes, pero diferente la manera de alcanzarlos. Generalmente, cabe destacar que en educación primaria existe una tendencia a desarrollar actividades relacionadas con la IE a través de técnicas propias del aprendizaje cooperativo, de las cuales se han obtenido resultados positivos durante los últimos años (Rivera-Pérez et al, 2021;Torrego-Seijo et al, 2020). Asimismo, son diferentes las propuestas de IE que se han desarrollado en primaria a partir de metodologías o estrategias lúdicas como la gamificación http://doi.org/10.15359/ree.25-3.6 http://www.una.ac.cr/educare educare@una.ac.cr Los artículos de la Revista Electrónica Educare del Centro de Investigación y Docencia en Educación de la Universidad Nacional, Costa Rica, se comparten bajo términos de la Licencia Creative Commons: Reconocimiento, No Comercial, Sin Obra Derivada 3.0 Costa Rica.…”
Section: La Educación De La Inteligencia Emocionalunclassified